COLORATION AND DISCOLORATION OF OLVEOLAR BONE AND TOOTH ENAMEL CAUSED BY MEDICATION - Giurgiu Cristian Levente; George Morarasu; Nicolae Baranov; Pogăcian-Maier Alexandra-Camelia; Radu-Mircea Sireteanu-Cucui; Cristina Pipa; Alina Monica Miftode; Alina Stefanache (Romanian Journal of Oral Rehabilitation)
Aim of the Study: This review aims to investigate the pharmacologically induced discoloration of teeth and bones, focusing on how various medications affect the coloration of tooth enamel and dentin. The study seeks to provide insight into the mechanisms behind intrinsic and extrinsic discoloration and their clinical implications.